Profil Resiliensi Karir Lulusan Smk Negeri - Emi, Emi; Kiswanto, Andi (Bimbingan dan Konseling, FKIP, Universitas Nahdlatul Ulama Cirebon, 2023)
Career guidance provided by guidance and counseling teachers in SMK (Senior High School) with the topic of career resilience profile, aims to determine the career resilience of SMK students which functions as an alternative support and information about the world of work. In developing resilience owned by SMK students, guidance and counseling teachers facilitate career guidance according to the needs of SMK students, and provide soft skills training in career guidance by utilizing media owned by the school, so that the goal of resilience of SMK graduates is expected to have adaptability, independence, confidence that they are capable in any work environment. With the existence of career guidance for SMK students, it is hoped that SMK graduates will have a good resilience profile, this will also have a good impact on reducing the number of unemployed in Indonesia.